Credible corporate social responsibility (CSR) communication predicts legitimacy: Evidence from an experimental study. (13th February 2019) - Lock, Irina; Schulz-Knappe, Charlotte
Abstract : Purpose: Companies in challenged industries such as fashion often struggle to communicate credibly with their stakeholders about their social and environmental achievements. Credible corporate social responsibility (CSR) communication, however, has been described theoretically as a predictor of legitimacy for organizations in society, but never proven empirically. The purpose of this paper is to test perceived credibility of a CSR website as a main predictor of input and output (pragmatic, cognitive and moral) legitimacy. Design/methodology/approach: A 2 × 2 between-subjects online experiment with participants recruited from the SoSci Panel ( n =321) is conducted on an anonymized website of a fashion company. Findings: Credible CSR websites result in output (cognitive and pragmatic) legitimacy. However, participation in the CSR decision-making process (input or moral legitimacy) did not matter. Instead, the more subjects accepted the outcome of the CSR communication process, the more they found a company to be legitimate. Research limitations/implications: The CSR communication process on a website is just one specific example. In other settings, such as social media, the role of participation in the CSR communication process will be different. Practical implications: Communicating credibly is a key, particularly in challenged industries, such as fashion. Thus, designing credible communication material matters for legitimacy. Originality/value: The findings for the first time confirm the credibility–legitimacy link in corporate communication empirically. Participation in CSR-related decision-making processes is overrated: the outcome of the CSR communication process is important for stakeholders and their acceptance of a company in society, the participation in the process less. This confirms the idea of CSR as stakeholder expectations management.